The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0203184
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of motivations for meditation in anthroposophic practitioners

Abstract: Research on meditation is advancing, but few studies about the motivations of meditators exist. Additionally, many forms and traditions of meditation have yet to be investigated. This study addresses both of these issues by presenting an overview of different forms of motivations found in contemporary Anthroposophic meditation practice. 30 Anthroposophic meditators were interviewed about their meditation experiences. The interviews were examined using thematic analysis. 14 data-driven themes were extracted and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…Participants in Shapiro's (1992) study obviously had such as spiritual background and also Schmidt's (2014) participants might largely fall into that category, whereas for the sample of meditators examined in Pepping et al's (2016) survey, this seems not to have been the case. The sample of Sparby and Ott (2018), who uniquely identified service to the world and humanity as an important reason, might be regarded as an especially homogeneous group that was highly influenced by their anthroposophic background. And last, the high importance given to reducing negative experiences (94.7%) in Pepping et al's (2016) sample might be partly responsible for the high attrition rate observed there, which might have been connected to high levels of neuroticism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants in Shapiro's (1992) study obviously had such as spiritual background and also Schmidt's (2014) participants might largely fall into that category, whereas for the sample of meditators examined in Pepping et al's (2016) survey, this seems not to have been the case. The sample of Sparby and Ott (2018), who uniquely identified service to the world and humanity as an important reason, might be regarded as an especially homogeneous group that was highly influenced by their anthroposophic background. And last, the high importance given to reducing negative experiences (94.7%) in Pepping et al's (2016) sample might be partly responsible for the high attrition rate observed there, which might have been connected to high levels of neuroticism.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a recent qualitative study (Sparby & Ott, 2018) focused on anthroposophical meditation and obtained only a partial match with Shapiro's (1992) three topics. In part probably due to anthroposophical practitioners' special kind of spiritual background, they found predominantly spiritual themes, and their analysis yielded a classification system of three categories: internal (inside the subject, e.g., selfrealization or initiation), external ("outside" the subject, e.g., duty), and service (meditating for something or someone other than oneself, e.g., service to the world and humanity).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most practitioners mainly meditate alone, working with books as the main source of instruction. Indeed, the tension between the potential of "higher knowledge", which is the most prominent form of motivation in the present sample (Sparby 2018b), and general lack of realization of this potential, is one of the most characteristic themes emerging from the interviews. Some participants describe confusion or frustration with the apparent lack of results coming from their meditation practice.…”
Section: Discussionmentioning
confidence: 88%
“…The following gives an overview of the method used in this project. A more in-depth description is available elsewhere (Sparby 2018b). Since the effects of Anthroposophic meditation have not been investigated previously, a qualitative methodology was chosen which is well suited to exploring new areas of enquiry (Given 2008;Tewksbury 2015;Velmans 2000).…”
Section: Methods and Participantsmentioning
confidence: 99%